A Modular Architecture Proposal for Multi-Turn Conversational RAG Systems - Dutra, Guilherme C.; Caraíba, André Felipe dos S.; Matos, João Pedro A. F.; Silva, Nádia F. F. da; Fernandes, Deborah S. A.; Oliveira, Sávio S. T. de (Anais da Escola Regional de Informática de Goiás (ERI-GO); 2025: Anais da XIII Escola Regional de Informática de GoiásDO - 10.5753/erigo.2025.17155, 2025)
Conversational systems face growing challenges in understanding context, resolving references, and maintaining coherence across multiple user turns. The SemEval-2026 Task 8 [Katsis et al. 2026] challenges participants to build conversational Retrieval-Augmented Generation (RAG) systems capable of handling multi-turn interactions with context dependencies, coreferences, and diverse question types. We propose a modular architecture combining five complementary strategies: (1) CoT query rewriting with multi-query diversification; (2) hybrid BM25+dense search; (3) rerank relevant documents; (4) answerability detection; and (5) specialized guardrails. Our contribution demonstrates how systematic integration of classical IR techniques with advanced prompting tackles SemEval-2026 Task 8 requirements.